Neutrophils Promote Larynx Squamous Cell Carcinoma Progression via Activating the IL-17/JAK/STAT3 Pathway - Tianyi Liu; Shimin Zong; Yang Jiang; Rui Zhao; Jie Wang; Qingquan Hua (Journal of Immunology Research)
Laryngeal squamous cell carcinoma (LSCC) is the main type of laryngeal cancer with poor prognosis. Incidence of LSCC increases every year, posing a great threat to human health. The underlying mechanism needs further study. Neutrophils are the most prevalent type of immune cells, which play vital roles in crosstalk between the microenvironment and cancer cells. In our study, we aim to figure out the complex regulation between neutrophils and LSCC. Our experiments showed that LSCC cells could promote the activation and mobility of neutrophils. And, in return, neutrophils enhanced the proliferation, migration, and invasion of LSCC. The subsequent results showed that IL-17 was highly expressed in neutrophil conditioned medium. Block of IL-17 could effectively inhibit the progression of LSCC induced by neutrophils. What is more, the results showed that IL-17 activated the JAK/STAT3 pathway in LSCC. Inhibition of the JAK/STAT3 pathway could significantly block neutrophil-induced LSCC progression. Our research reveals the complex interaction between neutrophils and LSCC cells, providing new ideas for the treatment of LSCC.